2018
DOI: 10.3390/ani8020027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Excluding Food Guarding from a Standardized Behavioral Canine Assessment in Animal Shelters

Abstract: Simple SummaryRecent research has called into question the value of the food guarding assessment as a predictive tool for determining the safety of shelter dogs. This study examined the effect of eliminating the food guarding assessment in nine U.S. animal shelters. It was found that when the food guarding assessment was removed, bites or other injuries to staff or adopters did not increase. However, dogs exhibiting food guarding behavior were less likely to be adopted, had a longer shelter stay, and were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 4 publications
3
25
1
Order By: Relevance
“…There are few studies on the ability of an assessment to reflect previous home behaviour; rather, most literature looks at predicting future behaviour [ 8 , 13 , 14 , 25 , 31 , 32 , 33 , 34 , 35 ]. In this study, behaviour reported in the home showed a relationship with certain aspects of the behavioural assessment including fear, friendliness, anxiety, arousal and aggression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies on the ability of an assessment to reflect previous home behaviour; rather, most literature looks at predicting future behaviour [ 8 , 13 , 14 , 25 , 31 , 32 , 33 , 34 , 35 ]. In this study, behaviour reported in the home showed a relationship with certain aspects of the behavioural assessment including fear, friendliness, anxiety, arousal and aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Possessive behaviour has been reported in the literature to have a low predictability [ 13 , 14 , 31 ]. This may be due to the manifestation of the problem being environmentally based [ 13 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing acceptance that food aggression by dogs may be considered normal regardless of cause, many shelters euthanize dogs who display such aggression to people [4,5]. In an animal shelter and in a home, such behavior is a potential risk to human safety.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a behavior that is often situation or environment-specific, responsive to treatment, and readily managed in a home [3,4]. Dogs displaying food aggression are not more likely to be returned by adopters than dogs that are not food aggressive [5]. Better understanding of the causation and prevalence of food aggression across various shelter dog subpopulations may lead to more emphasis on treating and managing the behavior, and fewer dogs being euthanized because of it.…”
Section: Introductionmentioning
confidence: 99%